The Ambiguity of Norms Regarding the Cancellation of Arbitration Awards in Law Number 30 Of 1999 Concerning Arbitration and Alternative Dispute Resolution and its Implications for Legal Certainty - Ryan Adhi Pradana; Evita Isretno Israhadi (Ridwan Institute, 2026)
The development of arbitration as an alternative dispute resolution mechanism in Indonesia is intended to provide a fast, efficient, and legally certain settlement process outside the court system. However, the regulation concerning the annulment of arbitration awards under Article 70 of Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution contains normative ambiguity, particularly regarding the interpretation of false documents, concealed documents, and fraudulent conduct as grounds for annulment. This condition creates uncertainty in judicial practice and potentially weakens the final and binding nature of arbitration awards. This study aimed to examine the ambiguity of arbitration award annulment provisions, analyze their implications for legal certainty, and formulate a normative reconstruction model to strengthen arbitration governance in Indonesia. This research employed a normative juridical method using statutory and conceptual approaches. The study analyzed primary legal materials, including Law Number 30 of 1999, the 1945 Constitution, relevant court decisions, and international arbitration standards, supported by legal doctrines and academic literature. The findings indicated that Article 70 contains grammatical, systematic, and teleological ambiguities arising from unclear definitions and the absence of explicit evidentiary standards concerning the existence of criminal elements. These ambiguities contribute to inconsistent judicial interpretations and excessive court intervention in arbitration proceedings. The study concluded that the reformulation of Article 70 was necessary by clarifying the meaning of annulment grounds, establishing clear standards of proof, and reaffirming the principle of minimal court intervention to ensure legal certainty and strengthen the effectiveness of arbitration in Indonesia